Understanding the Cost of Achieving the Sustainable Development Goals - Vorisek, Dana; Yu, Shu (World Bank, Washington, DC, 2020)
This paper presents a review of studies that estimate the cost of achieving the Sustainable Development Goals. Although the Sustainable Development Goals provide useful benchmarks for fiscal authorities and donors, typical cross-country costing exercises can be misleading, for a variety of reasons: double counting, sensitivity to underlying assumptions, downplaying the critical role of policy and institutions in advancing toward the goals, failure to discount costs or consider operation and maintenance costs in a consistent manner, and overlooking the tendency for different types of Sustainable Development Goal–related spending to have distinct effects. Recent costing studies by the World Bank Group have been developed to minimize the drawbacks of earlier studies. The paper also briefly reviews how the World Bank Group engages with stakeholders on the Sustainable Development Goals agenda.